Stakeholder’s Perspectives of the Twenty-First Century Skills - Mahmud, Malissa Maria; Wong, Shiau Foong (Frontiers in Education, 2022)
Today, the shift towards technology industries has made the applicable skills in high demand in the workforce. However, job training and education in general have not changed enough to keep up with the on-going trends. Concerns over the skills gap in our global workforce have exploded. In response to the demands of labour market and to close the skills gap, educational institution should focus on supporting skill development to cultivate the competencies that students need, making education in 21st century skills essential to prepare the students for the new and unknown in this fast-changing world of technology. This research aims to investigate the importance of 21st century skills for the employability of undergraduate students. The findings indicate that 21st century skills are the needed employability attributes, which transcend beyond qualifications and experience, that employers are looking for. It is also discovered from this study that the most effective way to attain 21st century skill is to focus on integrating 21st century knowledge and skills into the education support systems for our nation to realise its goal of successfully meeting the challenge of the 21st century.